Effect of fluticasone propionate on virus-induced airways inflammation and anti-viral immune responses in mice. (26th February 2015) - Singanayagam, Aran; Glanville, Nicholas; Bartlett, Nathan; Johnston, Sebastian
Abstract: Background: Inhaled corticosteroids are commonly used in the treatment of asthma and chronic obstructive pulmonary disease, but their effects on viral loads and anti-viral responses are poorly characterised. The aim of this study was to assess effects of inhaled fluticasone propionate on rhinovirus infection in vivo, in a mouse model. We tested the hypothesis that this treatment would reduce virus-induced airways inflammation but that the effect would be confounded by interference with anti-viral immune responses, leading to delayed viral clearance. Methods: C57BL/6 mice were intranasally dosed with fluticasone propionate (1 mg/kg) or vehicle (dimethyl sulfoxide, control), 1 h before infection with rhinovirus 1B. We assessed bronchoalveolar lavage (BAL) inflammatory cell numbers, and measured gene expression, protein production of innate mediators, or both by quantitative RT-PCR or ELISA. We compared mice treated with fluticasone with controls at various timepoints after infection. In additional experiments, recombinant interferon (IFN) beta was administered with fluticasone and rhinovirus 1B in both groups of mice. Findings: At 24 h post infection, fluticasone treatment suppressed rhinovirus induction of type I and III IFNs in the airways (for the fluticasone-treated group compared with controls: mean IFNβ BAL protein 20·2 pg/mL [SD 16·7] vs 103·0 [30·9]; mean IFNλ BAL protein 102·6 pg/mL [17·4] vs 217 [44·6], p<0·001); it also impaired viral clearance, with increased lung tissue viral RNA copy numbers (4·7 × 10 5 copies [SD 1·3] vs 2·6 × 10 5 [0·8], p<0·001). Despite increasing viral loads, fluticasone inhibited rhinovirus-induced airway inflammation as evidenced by suppressed BAL neutrophil numbers in fluticasone compared with control mice (0·021 × 10 5 [0·012] vs 0·59 ×  5 [0·39], p<0·001) and by suppressed lymphocyte numbers (0·092 × 10 5 [0·044] vs 0·45 × 10 5 [0·11], p<0·001). By contrast, fluticasone increased MUC5AC proteins (158·2 arbitrary units [29·9] vs 107·6 [7·1], p=0·0165) and MUC5B proteins (623·8 arbitrary units [231·9] vs 413·5 [70·5], p=0·0476) in BAL at day 7 post infection. Administration of intranasal recombinant IFN beta (10 4 units) with fluticasone and rhinovirus 1B led to upregulation of interferon-inducible cytokines OAS and CXCL10/IP-10 compared with control mice treated with fluticasone and rhinovirus alone and improved viral clearance without having any effect on suppression of inflammation by fluticasone. Interpretation: Our findings suggest that fluticasone treatment suppresses rhinovirus-induced airways inflammation in vivo but also impairs anti-viral immune responses and increases viral titres, leading to mucus hypersecretion. Since asthma and chronic obstructive pulmonary disease are both associated with inherent deficient IFN responses to rhinovirus, inhaled corticosteroids might interact synergistically with disease to inhibit IFN and thus lead to increased severity of exacerbation. The clinical applicability of these findings requires confirmation in human models of disease. Funding: Wellcome Trust.